Penser politiquement la communication publique - François Demers; Julien Rueff (Communication)
The syntagma “public communication” refers to a field of study concerned with the manifold and variable manifestations of public speech. This article examines a number of assumptions shared by studies in public communication in the aim of assessing how closely they correspond with the intention of rendering these communication phenomena politically intelligible. In light of Antonio Gramsci’s political thought, the authors analyze the extent to which these assumptions allow us to think about the compenetration of coercive and discursive modalities of power, the irreducible and irresolvable antagonisms between social groups, as well as the links between civil society and politics.